Ultrasensitive Photodetection in MoS2 Avalanche Phototransistors. Issue 19 (8th August 2021) - Seo, Junseok; Lee, Jin Hee; Pak, Jinsu; Cho, Kyungjune; Kim, Jae‐Keun; Kim, Jaeyoung; Jang, Juntae; Ahn, Heebeom; Lim, Seong Chu; Chung, Seungjun; Kang, Keehoon; Lee, Takhee
Abstract: Recently, there have been numerous studies on utilizing surface treatments or photosensitizing layers to improve photodetectors based on 2D materials. Meanwhile, avalanche breakdown phenomenon has provided an ultimate high‐gain route toward photodetection in the form of single‐photon detectors. Here, the authors report ultrasensitive avalanche phototransistors based on monolayer MoS2 synthesized by chemical vapor deposition. A lower critical field for the electrical breakdown under illumination shows strong evidence for avalanche breakdown initiated by photogenerated carriers in MoS2 channel. By utilizing the photo‐initiated carrier multiplication, their avalanche photodetectors exhibit the maximum responsivity of ≈3.4 × 10 7 A W −1 and the detectivity of ≈4.3 × 10 16 Jones under a low dark current, which are a few orders of magnitudes higher than the highest values reported previously, despite the absence of any additional chemical treatments or photosensitizing layers. The realization of both the ultrahigh photoresponsivity and detectivity is attributed to the interplay between the carrier multiplication by avalanche breakdown and carrier injection across a Schottky barrier between the channel and metal electrodes. This work presents a simple and powerful method to enhance the performance of photodetectors based on carrier multiplication phenomena in 2D materials and provides the underlying physics of atomically thin avalanche photodetectors. Abstract : The authors demonstrate ultrasensitive MoS2 avalanche phototransistors by studying avalanche carrier multiplications under light illumination. By operating MoS2 transistors at a high source–drain voltage, they identify an optimal regime where photoresponsivity and detectivity simultaneously outperform previously reported values. Their work provides a powerful strategy to improve the performance of 2D‐materials‐based phototransistors and shows the potential of atomically thin avalanche photodetectors.